Pengelolaan Daun Kering untuk Dijadikan sebagai Pupuk Kompos - Halimatussa’diyah, Enni; Dwi, Citra Partika; Balqis, Zia Syamsiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A substance administered to plants with the intention of enhancing nutrient availability is referred to as fertilizer. The goal of this study project was to find a solution to the issue of environmental contamination brought on by the buildup of dry leaf detritus. Compost is created using dry leaf waste as the primary component and EM4 as an aid.EM4 is responsible for breaking down the organic material in leaves. The characteristics of the pre-made dry leaf compost are its blackish brown hue, crumbly and somewhat rough texture, lack of odor, and loose granular shape. The method of research used is library research, or research that is based on printed books and journals that are accessible on Google Scoolar. This type of study is a descriptive analysis that draws on the works of authors who have expertise in relevant disciplines and other studies that are descriptive in nature. Using data gathered through the inductive method, generalizations are then analyzed using one or more initial data sets. The acquired data was examined using a descriptive analytic approach. By turning dry leaves into compost that is more beneficial and valuable economically, this research also aims to strengthen and expand the community's creative capacities as well as its economics. Bright colors are a sign of overly dry composting or a humidity level below 30%. One factor in determining a compost's maturity is aroma. The compost fermentation process will produce a variety of strong aromas. Keywords: Utilization of waste, compost, dry leaves, EM4